2009
DOI: 10.5539/ibr.v1n3p67
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Determinants and Outcomes of Superior Downward Influence Tactics: The Mediating Impact of Role Ambiguity and Subordinates’ Competence Level

Abstract: This paper examines the antecedents and consequences of superior downward influence tactics in Malaysian companies. The literature review revealed that downward influence tactics are useful but practically challenging. Researchers have identified downward influence tactics such as inspirational appeal, consultation, exchange, pressure, ingratiation, and rational persuasion as commonly used influence tactics by superior to change the behavior of subordinates. The purpose of this paper is to develop a conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 91 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Based on the interviews with the participants in her study, Chong (2014) found that managers often use ingratiation and exchange tactics. Lee and Salleh (2009) argue that supervisors may use downward influence tactics because of subordinates' competence level. In regard to high subordinate competence, supervisors may use downward influence tactics such as consultation (Lee & Salleh, 2009;Deniz et al, 2018).…”
Section: The Relationship Between Employee Competency and Downward Influence Tacticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the interviews with the participants in her study, Chong (2014) found that managers often use ingratiation and exchange tactics. Lee and Salleh (2009) argue that supervisors may use downward influence tactics because of subordinates' competence level. In regard to high subordinate competence, supervisors may use downward influence tactics such as consultation (Lee & Salleh, 2009;Deniz et al, 2018).…”
Section: The Relationship Between Employee Competency and Downward Influence Tacticsmentioning
confidence: 99%
“…Lee and Salleh (2009) argue that supervisors may use downward influence tactics because of subordinates' competence level. In regard to high subordinate competence, supervisors may use downward influence tactics such as consultation (Lee & Salleh, 2009;Deniz et al, 2018). Since consultation and exchange tactics allow supervisors and subordinates to communicate and share information (Kim & Gausdal, 2020), this tactic may be suitable for competent subordinates.…”
Section: The Relationship Between Employee Competency and Downward Influence Tacticsmentioning
confidence: 99%
See 2 more Smart Citations